Penentuan Tingkat Kepuasan Konsumen Dalam Memilih Air Minum Dalam Kemasan Galon Dengan Metode AHP - Ratih Adinda Destari; Asbon Hendra Azhar; Wahyu Sapta Negoro (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
The use of drinking water in gallons for consumers at this time in Indonesia has greatly increased. Every day consumers need healthy drinking water and of course it is very easy to get and affordable. Not to mention that at this time it is very difficult to get drinking water products in gallons that actually meet the health standards that have been set. For this reason, a solution is needed to get priority drinking water in gallon packages that are affordable and the results are expected to meet the targets expected by consumers. The method used in decision making in this study can later become a reference for the community in choosing reliable Gallon Bottled Drinking Water where the method used is the AHP Decision Support System, one of the methods developed by Prof. Thomas Lorie Saaty from the Wharton Business School in the early 1970s, was used to find a ranking or order of priority from various existing alternatives and analyzed to determine the priority of drinking water in gallons that would later be used by consumers. The results of the questionnaire research obtained bottled drinking water brands which were consumed by many people in Medan City in this study, namely Aqua 42,9436%, Cleo  35,8243 % and  Le Minerale 21,2321 %